THE ONSET OF ANCA-ASSOCIATED SYSTEMIC VASCULITIS MASKING RHEUMATOID ARTHRITIS - N. F. Frolova; L. V. Korsakova; E. S. Stolyarevich; N. O. Nikonorova; T. V. Beketova (Научно-практическая ревматология)
The paper describes a case of microscopic polyangiitis (MPA), the first clinical manifestation of which has been joint damage characterized chiefly by arthralgias. The overproduction of rheumatoid factor and anticyclic citrullinated peptide antibodies served as the basis for assuming rheumatoid arthritis (RA). Two years after disease onset, there were the first signs of glomerulonephritis (GN) that further progressed to severe kidney failure. MPA was diagnosed by a renal biopsy that revealed the morphological pattern of immunonegative GN with glomerular crescents. The diagnosis was verified by the presence of serum antineutrophil cytoplasmic antibodies (ANCA). There were no X-ray bone changes typical for RA at a 10-year follow-up. The paper discusses whether it is important to incorporate ANCA-associated systemic vasculitis into a diagnostic search in patients with early arthritis, particularly when the latter is concurrent with involvement of the kidney or other organs.